National Health Insurance (BPJS) in Indonesia: An Islamic Perspective on Value Creation, Engagement, and Satisfaction - Fatchan Achyani; Ilham Nuryana Fatchan; Fuad Hudaya Fatchan (Universitas Bangka Belitung, 2026)
This study analyzes how the service quality of BPJS Health influences customer engagement (CustEngagement) and customer loyalty (CustLoyalty) in the context of PKU Muhammadiyah Hospital in Indonesia, with patient satisfaction as the main mediator. Using primary data from 296 BPJS inpatient respondents at PKU Muhammadiyah Hospital that collaborates with BPJS, the CARTER model (Compliance, Assurance, Reliability, Tangible, Empathy, Responsiveness) combined with satisfaction and engagement dimensions is analyzed using PLS-SEM.The main results show that the paths from Satisfaction to CustEngagement and Satisfaction to CustLoyalty are positively significant (coefficients of approximately 0.272–0.307; t-statistics > 3.5; p < 0.05), confirming that higher patient satisfaction directly increases the level of engagement and the tendency toward loyalty to health service facilities. On the other hand, Responsiveness acts as the primary driver of satisfaction (coefficient to Satisfaction ≈ 0.897; t = 2.967; p = 0.003), which in turn enhances CustEngagement and CustLoyalty through the mediating role of Satisfaction.The other dimensions (Assurance, Compliance, Empathy, Reliability, Tangible) do not show a significant direct effect on Satisfaction or CustEngagement in this model, indicating that the BPJS context at PKU Muhammadiyah Hospital may require additional mediators/moderators or sharper indicators. Contextually, these findings instead highlight the importance of strengthening the responsiveness dimension and harmonizing it with values of empathy, friendliness, and justice grounded in sharia principles in every service interaction. A responsive yet warm and fair approach is expected to enrich patients’ experiences, foster feelings of being valued and trusted, and ultimately strengthen their attachment and loyalty to PKU Muhammadiyah Hospital.